Does testing for coronavirus reduce deaths? - Weshah A. Razzak (Economics and Econometrics Research Institute (EERI), 2020)
We examine the effect of testing for Coronavirus on deaths in eight countries over the month of March 2020 by estimating a fixed-effect regression model using the Generalized Method of Moments (GMM). On average, the data reject the hypothesis that "testing" for the virus does not affect death. By country, however, we reject the hypothesis in two countries at the 5 percent level, in three countries at the 10 percent level, and could not reject it in three other countries. On average, testing for the virus is an important element of the health policy.
Keywords: I10; C23; C26; 330; Pandemic; Testing and Deaths; Panel Data; Fixed Effect Model; GMM